Non-Fungible Tokens as Jurisdictionless Innovation: Legal Vacuum, Loopholes, Potentials and Solutions - Yongkie Yongkie; Hari Sutra Disemadi (Widya Yuridika, 2023)
Non-Fungible Tokens (NFTs) are one of the technological innovations that provide convenience for every human being, especially in the context of business and economic opportunities. Features such as anonymity, decentralization, and its online scope are undeniably a double-edged knife phenomenon. On the one hand, it makes things easier, but on the other hand, it has the potential to become a platform for criminal acts such as money laundering, personal data violations, and copyright plagiarism. So that the urgency of special regulations should be considered, but with a progressive nature and paradigm so that NFT innovation does not die just because the law does not adjust to the times. Progressive law is a solution and answer to the phenomena that occur, where the legal paradigm and its enforcement must be in accordance with the moral system, the times, and the values that live in society to achieve substantive justice. Practical breakthroughs such as utilizing the latest technology can be developed to assist the law enforcement process in cyberspace.